2017
DOI: 10.18290/rpsych.2017.20.2-5en
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Polish experimental short version of the Young Schema Questionnaire (YSQ-ES-PL) for the assessment of early maladaptive schemas

Abstract: The Young Schema Questionnaire (YSQ) measures the intensity of early maladaptive schemas connected with symptoms of mental disorders, particularly personality disorders. We conducted a procedure of shortening the Polish version of the YSQ, analogous to the original one, and determined the psychometric properties of the instrument thus developed by performing a reliability and validity analysis (n = 1.073). In the second part of the study we tested the factor structure of the YSQ using confirmatory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The schema questionnaire is a tool used in this therapeutic approach, whereas and the Schema Questionnaire-Short Form ( SQ-SF ) is a very useful instrument for measuring EMSs [ 37 ]. Lee et al [ 30 ] analyzed the psychometric properties of this questionnaire in South Korea, Staniaszek and Popiel [ 56 ] in Poland, Lyrakos [ 32 ] in Greece, Kriston et al [ 27 ] in Germany, Cazassa and Oliveira [ 10 ] in Brazil, Rijkeboer and van den Bergh [ 44 ] in the Netherlands, and [ 55 ] in Romania, All of them reported the psychometric properties of the SQ-SF to be appropriate. Kriston et al [ 28 ] reported no clear evidence confirming the schema domains.…”
Section: Introductionmentioning
confidence: 99%
“…The schema questionnaire is a tool used in this therapeutic approach, whereas and the Schema Questionnaire-Short Form ( SQ-SF ) is a very useful instrument for measuring EMSs [ 37 ]. Lee et al [ 30 ] analyzed the psychometric properties of this questionnaire in South Korea, Staniaszek and Popiel [ 56 ] in Poland, Lyrakos [ 32 ] in Greece, Kriston et al [ 27 ] in Germany, Cazassa and Oliveira [ 10 ] in Brazil, Rijkeboer and van den Bergh [ 44 ] in the Netherlands, and [ 55 ] in Romania, All of them reported the psychometric properties of the SQ-SF to be appropriate. Kriston et al [ 28 ] reported no clear evidence confirming the schema domains.…”
Section: Introductionmentioning
confidence: 99%
“…Bloo, Arntz, and Schouten (2017) describe an instrument making it possible to assess the complex psychopathology of borderline personality disorder and to monitor the changes that occur over time. Two other texts (Zawadzki, Popiel, Pragłowska, & Newman, 2017;Staniaszek & Popiel, 2017) present instruments rooted in cognitive conceptions focused on the role of schemas in the psychopathology of personality disorders. Schemas understood as core beliefs characteristic for particular personality disorders are measured by means of the Personality Beliefs Questionnaire (PBQ) by A. T. Beck and colleagues, and the Polish versions of this instrument are described by Zawadzki, Popiel, Pragłowska, and Newman (2017).…”
mentioning
confidence: 99%
“…Young, play a significant role in the development and maintenance of pathological functioning in people with personality disorders are measured by the Young Schema Questionnaire (YSQ), whose short Polish experimental version is presented by Staniaszek and Popiel (2017). The series of texts devoted to instruments concludes with an article about a questionnaire enabling the assessment of personality disorders from the perspective of DSM-5 proposals (Strus, Rowiński, Cieciuch, Kowalska-Dąbrowska, Czuma, & Żechowski, 2017).…”
mentioning
confidence: 99%